A CNOX-like protein disulfide-thiol interchange activity of the cell surface of mouse sperm - Morré, D. James (Acta Biologica Szegediensis, 2006)
Intact frozen mouse sperm were analyzed for the presence of ECTO-NOX-like protein disulfide-thiol interchange activity. Activity was determined both from the cleavage of a dithiodipyridine substrate and from the restoration of activity to scrambled and inactive ribonuclease. An activity was found using both methods of activity determination. The activity was resistant to inhibition by both capsaicin and bacitracin. The activity, which oscillated in the characteristic manner of ECTO-NOX proteins, was characterized by a pattern of five maxima and an overall period length of 24 min. Three of the five maxima were separated by an interval of 6 min and the remaining maxima were separated by intervals of 4.5 min to generate the repeating pattern with a period length of 24 min. The activity pattern was unusual in that all five of the maxima within the 24 min repeat were of approximately equal specific activity. Normally, for somatic cells, the first two maxima are involved in NADH oxidation and less pronounced in terms of protein disulfide-thiol interchange than are the remaining three.